Thermal performance analysis of evacuated tubes solar air collector in Indian climate conditions. Issue 2 (3rd March 2016) - Kumar, Ashish; Kumar, Sanjeev; Yadav, Avadhesh
Abstract : The thermal performance of one-ended evacuated tubes solar air collector is experimentally investigated during the winter season at NIT Kurukshetra, India [29 ° 58 ′ (latitude) North and 76 ° 53  ′ (longitude) East]. The collector consists of 15 one-ended evacuated tubes with different lengths of directional inner aluminium tubes (inserted tubes) and a manifold channel, with air used as a working fluid. The inlet air flows through the directional inner aluminium tubes as a result of forced convection. In this experiment, evacuated tubes are used for producing hot air corresponding to different lengths of directional aluminium tubes without using any intermediate fluid. The temperature of the outlet air depends on the air flow rate, length of the directional aluminium tube and solar intensity. The maximum temperature difference between outlet air and inlet air at solar intensity 904 W/m 2 was found to be 72.7 °C with a flow rate of 5.06 kg/h and length of 0.83 m.